The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1516-44462011005000003
|View full text |Cite
|
Sign up to set email alerts
|

Associations between polymorphic variants of the tryptophan hydroxylase 2 gene and obsessive-compulsive disorder

Abstract: OBJECTIVE: A substantial body of evidence suggests that obsessive-compulsive disorder has a genetic component, and substantial candidate genes for the disorder have been investigated through association analyses. A particular emphasis has been placed on genes related to the serotonergic system, which is likely to play an important role in the pathogenesis of obsessive-compulsive disorder. The gene for tryptophan hydroxylase 2, which is a rate limiting enzyme in serotonin synthesis is considered an important ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…For this reason, there has been renewed interest in the search for ‘endophenotypes’ (i.e. cognition dysfunctions), which are measurable disease‐associated traits that have a simpler relationship with underlying genes than with clinical measures (da Rocha et al in press).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, there has been renewed interest in the search for ‘endophenotypes’ (i.e. cognition dysfunctions), which are measurable disease‐associated traits that have a simpler relationship with underlying genes than with clinical measures (da Rocha et al in press).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that changes in the 5-HT system were critical in children with ODD [39, 40]. Moreover, the polymorphisms of TPH - 2 have been shown to be associated with ADHD [16, 41, 42], obsessive–compulsive disorder [43], and bipolar affective disorder [44]. Also, TPH -2 was found to be associated with major depression [45] and pathogenesis of depression in Chinese females [46] and suicidal behavior [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed no significant differences in genotype frequency of the tryptophan hydroxylases TPH1 and TPH2 genes variants, encoding for the enzymes involved in serotonin synthesis (Delorme et al, 2006;Frisch et al, 2000;Han et al, 1999;Walitza et al, 2004). Conversely, other investigations reported haplotype association between TPH2 SNPs and the disorder (da Rocha et al, 2011;Mössner et al, 2006) or between rs4570625 and patients scrupulousness (Di Nocera et al, 2014).…”
Section: Serotonergic Systemmentioning
confidence: 92%
“…rs4680 ( Val158Met) COMT (Catechol-O-Methyltransferase) polymorphism was associated with OCD (S. ), gender-specifically (Alsobrook et al, 2002Denys et al, 2006a;Karayiorgou et al, 1997Karayiorgou et al, , 1999Melo-Felippe et al, 2016;Pooley et al, 2007;Poyurovsky et al, 2005;Taylor, 2013), depending on the age at onset (Tükel et al, 2013) or Y-BOCS (Yale-Brown Obsessive-Compulsive Scalethe most frequently used interview to rate the severity of symptoms (Goodman et al, 1989)) scores (Erdal et al, 2003), or in patients with alexithymia tracts (Koh et al, 2016). However, other reports did not find an association between rs4680 and OCD (Bellivier et al, 1998;Camarena et al, 2004;Cristina Cavallini et al, 1998;da Rocha et al, 2011;Delorme et al, 2006;Di Bella et al, 2002;Han et al, 1999;Mak et al, 2015;Mössner et al, 2006;Walitza et al, 2002).…”
Section: Dopaminergic Systemmentioning
confidence: 99%